A251 AZOXYMETHANE INDUCES INTESTINAL CRYPT ABSCESSES IN KAISO TRANSGENIC (KAISOTG ) MICE. (1st March 2018) - Bayer, L B; Robinson, S; Daniel, J
Abstract: Background: Colitis associated cancer (CAC) is a poorly characterized subgroup of colorectal cancer (CRC) that afflicts 20% patients suffering from inflammatory bowel disease (IBD). The limited understanding of CAC stems from the lack of suitable mammalian model systems, as well as a general gap in research involving the molecular mechanisms of this disease. Studies have shown that increased expression of the transcription factor Kaiso causes intestinal inflammation and tumorigenesis in mice. Aims: The objective of this research is to determine the effects of environmental carcinogens on disease progression (IBD to CAC) in Kaiso overexpressing transgenic ( Kaiso Tg ) mice. We hypothesize that treatment with the carcinogen, azoxymethane (AOM), will exacerbate the Kaiso-mediated intestinal inflammation and lead to colitis-associated cancer (i.e. polyp formation). Methods: We injected Kaiso Tg or wildtype (WT) mice with either AOM, or a PBS vehicle control once a week for 6 weeks and sacrificed them one week after the last injection. Their intestinal tissues have been collected and assessed macroscopically for inflammation and polyp formation. Immunohistochemistry (IHC) analysis was then performed for established inflammation- tumourigenesis-associated proteins (e.g. p53, NF-kB, p120 ctn, b-catenin). Results: Our preliminary findings show that the intestinal tissues of AOM-treated mice exhibited atypical hyperplasia and aberrant crypt foci (ACF), which represent precursors to polyp formation. The mice also exhibited a higher quantity of NF-kB positive nuclei compared to the control, indicating increased inflammation in the experimental group. Interestingly, Kaiso Tg mice were found to have decreased levels of acetylated-p53 (K381), indicating higher p53 survival rates in overexpressing mice. Conclusions: The findings from our pilot study suggests that the Kaiso Tg mouse model may hold potential as a novel genetic model for IBD-CAC progression, compared to the popular AOM/DSS mouse model that currently represents the gold standard for CAC. Kaiso Tg mice closely follow the natural inflammatory progression in mammals[SR1], and, when treated with AOM, can be used to molecularly characterize the transition from IBD to CAC. [SR2] Mice in our expanded study of AOM-treated Kaiso Tg will be examined in December 2017[SR3], and we anticipate that they will exhibit increased inflammation and phenotypes akin to CAC. Funding Agencies: NSERC, McMaster University